LEGAL DUE TO ADVANTAGE WITHOUT NOTARY NOTARY DECLARED FROM ISLAMIC LAW COMPILATIONS AND CODE OF CIVIL LAW - Taufiqurohman Taufiqurohman (Sultan Agung Notary Law Review, 2021)
Based on the description above, the objectives of this study are: to find out and explain wills without a Notary Deed in view of the KHI and the Civil Code; To find out and explain the similarities and differences of wills without a Notary Deed in view of the KHI and the Civil Code. The research approach used is normative juridical.The results obtained in this study are the legal consequences of wills without a notary deed, making the will prone to lawsuits from interested parties because the evidence is not strong enough and there is no legal certainty. By law, if a will is made without a notary deed or a testament under hand, the will cannot provide a guarantee of legal certainty because it can be canceled unilaterally. According to the Civil Code, wills can be revoked and can be canceled or canceled. As for the revocation of a will according to the KHI, among others, is regulated in Article 199. There are three ways to revoke a will according to the Civil Code, namely explicit revocation, secret revocation and revocation due to exile.Keywords: Legal Consequences, will, notary deed, compilation of Islamic law, civil law